(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
This study aimed to specify the best model that represents the stochastic process that generated the data of cow’s milk production in Tartous governorate. The goal was to identify the time trend status of production growth and forecast the future production of cow’s milk in Tartous. This was achieved by using Box-Jenkins methodology which based mainly on the stochastic models ARIMA, using annual time series during the period of 1988-2018. The study indicated that the series was stationary around a downward trend. So, milk production in Tartous was shrinking over time. The results concluded that ARIMA (2,0,0) with deterministic trend and constant term is the best model among other models based on specific statistical criterions and tests. The proposed model used to forecast milk production up to 2023. Forecasts indicated that production will continue to decline over the next few years.